Optimal Ni loading towards efficient CH4 production from H2 and CO2 over Ni supported onto fibrous SBA-15 - S. N., Bukhari; Chi, Cheng Chong; Setiabudi, H. D.; Nurul Aini, Razali; Aziz, M. A. A.; Jalil, A. A.; Chin, S. Y. (Elsevier, 2019)
The transformation of SBA-15 into fibrous type SBA-15 (F-SBA-15) as well as the influence of Ni loadings (1, 3, 5, and 10 wt%) towards an efficient CH4 production from H-2 and CO2 were explored. The synthesized catalysts were characterized using XRD, BET, ICP-MS, FTIR, FESEM-EDX, TEM, and in-situ FTIR adsorbed pyrrole. Increasing Ni loadings onto F-SBA-15 support promoted excellent performance towards CO2 methanation. The efficacy in CO2 methanation over Ni/F-SBA-15 increased with a sequence of 1%Ni/F-SBA-15 < 3%Ni/F-SBA-15 < 5%Ni/F-SBA-15 approximate to 10%Ni/F-SBA-15, indicating the superior performance and stability of 5%Ni/F-SBA-15. The increasing trend was due to the fibrous morphology of support which enhanced the quantity of Si-O-Ni bond, triggered better Ni dispersion, strengthen metal-support interaction, and increased the basicity. However, higher Ni loadings (10 wt %) onto F-SBA-15 slightly declined the performance and stability of CO2 methanation due to the limited spaces for substitution of Ni species with the silanol groups of F-SBA-15 upon the bulk Ni phase, poorer Ni dispersion, weaker metal-support interaction, and lower basicity. The new finding of combination between fibrous SBA-15 (F-SBA-15) with an optimum Ni loading contributed towards an outstanding performance and thus could be applied in various applications. (C) 2019 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.